Sejarah balai cerap di Malaysia : Kajian isu-isu pembangunan sumber manusia / Khadijah Ismail - Khadijah, Ismail (2015)

(untitled)
The history of the observatory showed a systematic organization in carrying out educational and research studies in astronomy since the early 9th century during the glorious Islamic civilization era. The Syammasiya and Qasiyun Observatory which were the earliest and other observatories during that era had been used as examples to European observatories and observatories worldwide including ones in Malaysia until today. Differences exist between the observatories in the past and at the present in the scopes of research and the instruments in use now which have given rise to the difference in the objectives and functions and the contributions of observatories especially those observatories in Malaysia. Although observatories in Malaysia have progressed, certain issues still prevail especially in matters pertaining to human resource development. Consequently, the research aims at evaluating the history of observatories in Malaysia and analysing issues of human resource development that have resulted from it. This research also puts forward solutions based on human resource theories to the issues of human resource in observatories around Malaysia. Data collection for the qualitative research was conducted using documentation, interviews and observation methods. A comparative analysis of the data was conducted by making comparisons and employing the inductive and deductive methods. The results indicate that although these observatories have contributed towards education and studies of the new moon, weaknesses exist prominently in the field of human resource compared to those observatories during the glorious era of Islamic civilization, in the aspect of expertise development and transfer of experience. Based on analyses on human resource at Malaysian observatories, in general, it was found that these observatories, on the whole, iv provide effective training and learning programmes aimed at developing the skills needed by these workers, despite problems that exist in its support system and the environment of these observatories which are not totally capable in providing training and the development of human resource for researchers and the staff at the observatories in Malaysia and the lack of experts who could transform these observatories into research centers. A strategic human resource plan has never been discussed seriously and students of astronomy has not been exposed to opportunities to the optimum. The system of recruitment and transfer of experience practiced in observatories in Malaysia are found to be unsuitable. Among the suggestions are to improve the system of recruitment by hiring workers and researchers with genuine interest, knowledge and skills apart from training these researchers and experts in astronomy to develop observatories as research and educational centres. It is hoped that this study will provide beneficial input for administrators and the staff of observatories and policy makers in the field of science and technology particularly astronomy in efforts to build observatories.